2015
DOI: 10.1182/blood-2014-06-582759
|View full text |Cite
|
Sign up to set email alerts
|

Inter-α inhibitor protein and its associated glycosaminoglycans protect against histone-induced injury

Abstract: Extracellular histones are mediators of tissue injury and organ dysfunction; therefore they constitute potential therapeutic targets in sepsis, inflammation, and thrombosis. Histone cytotoxicity in vitro decreases in the presence of plasma. Here, we demonstrate that plasma inter-α inhibitor protein (IAIP) neutralizes the cytotoxic effects of histones and decreases histone-induced platelet aggregation. These effects are mediated through the negatively charged glycosaminoglycans (GAGs) chondroitin sulfate and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 62 publications
(95 reference statements)
0
76
0
Order By: Relevance
“…Not surprisingly, many plasma proteins that neutralize histones are highly negatively charged, such as heparin, 44 pentraxin-3, 45 C-reactive protein, 46 and inter-a inhibitor protein. 21 DNA may also efficiently neutralize the histone charge, and indeed, analogous to nucleosomes, we showed that both ssDNA and dsDNA neutralized the cytotoxicity induced by histones. In support of our results, it was nuclease (5000 U/mL) at 37°C for 1 hour to digest nucleosome DNA before incubation with serum (50%) from 5 healthy donors at 37°C for 1 hour.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Not surprisingly, many plasma proteins that neutralize histones are highly negatively charged, such as heparin, 44 pentraxin-3, 45 C-reactive protein, 46 and inter-a inhibitor protein. 21 DNA may also efficiently neutralize the histone charge, and indeed, analogous to nucleosomes, we showed that both ssDNA and dsDNA neutralized the cytotoxicity induced by histones. In support of our results, it was nuclease (5000 U/mL) at 37°C for 1 hour to digest nucleosome DNA before incubation with serum (50%) from 5 healthy donors at 37°C for 1 hour.…”
Section: Discussionmentioning
confidence: 60%
“…Although histone H3 was not degraded in FSAP-deficient serum, some histone neutralization occurred in the absence of FSAP, possibly as a result of histone neutralization by inter-a inhibitor protein or albumin. 20,21 In addition to FSAP, APC has been described to proteolyze histones. 11 In contrast to APC, FSAP becomes activated upon contact with dead cells and histones, supporting a role for FSAP in histone proteolysis in the absence of thrombin formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, CRP appears to be an endogenous modulator of the damaging effects of histones. The interalpha inhibitor protein in plasma and its associated glycosaminoglycans was also recently shown to bind to free histones and protect against injurious effects of histones in vitro and in vivo [102]. We have recently found that the host defense lectin, surfactant protein D, also binds to histones and reduces their ability to trigger neutrophil respiratory burst responses [Hoeksema et …”
Section: Platelet Activation and Thrombin Generation By Histonesmentioning
confidence: 99%
“…Intravenous infusion of exogenous, full-length glycosaminoglycans (including heparin (a highly-sulfated HS (2, 6)) or the chondroitin sulfate-rich Inter-alpha inhibitor (17)) attenuated histone-induced organ injury. Whether circulating (endothelial glycocalyx-derived) HS fragments would provide similar protective benefit is uncertain, however, particularly given reports that fragmented HS can propagate inflammation via activation of toll-like receptor signaling (18).…”
Section: Discussionmentioning
confidence: 99%